Peningkatan Keterampilan Akuntansi Berbasis Teknologi Informasi Bagi UMKM Batik Cirebon - Lailah Fujianti; Harimurti Wulandjani; Susilawati (SULUH: Jurnal Abdimas, 2019)
Accounting skills training for MSMEs is expected to be an orderly administration for partner MSMEs to accurately calculate the cost of production and to separate personal assets from business assets. The benefits for the Cirebon regional government are improving the quality of its human resources, increasing economic growth and PAD, reducing unemployment and poverty, reducing social inequality and disrupting security especially in the region. While the benefits for PPM-FEB-UP institutions contribute to the surrounding community and carry out the functions of the Higher Education Tridarma in the Field of Community Service which will provide added value to FEB-UP in particular and the academic community of Pancasila University in general.